Synthesis and Biological Activity of 4,6-Substituted aryl-1-acetyl pyrimidine-2-ols - Bamnela, Rita; Shrivastava, S.P. (Asian Journal of Chemistry, 2010)
The synthesis of 4-(4'-bromophenyl)-6-substituted aryl-1-acetyl-pyrimidine-2-ols have been reported. The synthesized derivatives were characterized by elemental analysis and spectral data (IR and 1H NMR). All the synthesized derivatives have been evaluated for their antimicrobial and anthelmintic activities against microbes and helminthes.